Beyond germline genetic testing - heterozygous pathogenic variants in PMS2 in two children with Osteosarcoma and Ependymoma - Michaela Kuhlen; Mariola Monika Golas; Tina Schaller; Nicole Stadler; Felicitas Maier; Olaf Witt; Michael C. Frühwald (Hereditary Cancer in Clinical Practice, 2023)
Abstract Background Lynch syndrome (LS) is not considered part of childhood cancer predisposition syndromes. Case presentation Analysis of a pediatric osteosarcoma (OS) displayed hypermutation (16.8), alternative lengthening of telomeres (ALT), loss of PMS2 expression in tumor tissue (retained in non-neoplastic cells), PMS2 loss of heterozygosity (LOH), and high-degree of microsatellite instability (MSI) tested by PCR. A heterozygous duplication c.1076dup p.(Leu359Phefs*6) in exon 10 of NM_000535.6:PMS2 was detected by SNV analysis in peripheral blood, confirming diagnosis of LS in the patient. The tumor molecular features suggest LS-associated development of OS. In a second case, whole-genome sequencing identified a heterozygous SNV c.1 A > T p.? in exon 1 of PMS2 in tumor and germline material of a girl with ependymoma. Tumor analysis displayed evidence for ALT and low mutational burden (0.6), PMS2 expression was retained, MSI was low. Multiplex ligation-dependent probe amplification identified no additional PMS2 variant and germline MSI testing did not reveal increased gMSI ratios in the patient´s lymphocytes. Thus, CMMRD was most closely excluded and our data do not suggest that ependymoma was related to LS in the child. Conclusions Our data suggest that the LS cancer spectrum may include childhood cancer. The importance of LS in pediatric cancers necessitates prospective data collection. Comprehensive molecular workup of tumor samples is necessary to explore the causal role of germline genetic variants.